PROFIL PASIEN PRESBIKUSIS POLI KLINIK THT-KL RUMAH SAKIT ISLAM SITI RAHMAH PADANG PERIODE JANUARI 2023-DESEMBER 2024 - Seres Triola; M. Anton Maulana; Rika Amran (Yayasan Nusantara Hasana Berdikari, 2026)
Presbycusis is a neural sensory hearing loss that is bilaterally symmetrical and occurs with age characterized by high frequency hearing loss. This hearing loss is progressive, irreversible, and symmetrical bilateral neurosensory hearing loss that often occurs in the elderly (>60 years). The purpose of this study was to determine the profile of presbycusis patients at Siti Rahmah Islamic Hospital Padang January 2023-December 2024. This study used a descriptive observational design with a cross sectional design using secondary data with total sampling technique. The number of samples used was 32 data with total sampling technique. In this study, data analysis was performed with univariate analysis using the Statistical Product and Service Solution (SPSS) 25 program. Of the 32 samples of data obtained, presbycusis patients with female gender, totaling 17 people (53.1%) were the most common results compared to men. Presbycusis patients with the highest age group ≥65 years, totaling 21 people (65.6%). Presbycusis patients with the highest frequency were comorbidities, totaling 25 people (78.13%) with the highest comorbidity being hypertension. Presbycusis patients with moderate hearing loss were found, totaling 13 people (40.6%) which was the highest result. Presbycusis patients were more common in women than men, with the largest proportion being in the age group ≥65 years, indicating a higher prevalence in the elderly. Most patients had comorbidities, especially hypertension, which was the dominant risk factor in this case. Most patients had a moderate degree of hearing loss, compared to mild, moderate severe and very severe categories. Early detection, education, and integrated management are needed to prevent complications and improve quality of life.